Sound technology and the American cinema : perception, representation, modernity - Lastra, James (Columbia University Press, 2000)
Representational technologies including photography, phonography, and the cinema have helped define modernity itself. Since the nineteenth century, these technologies have challenged our trust of sensory perception, given the ephemeral unprecedented parity with the eternal, and created profound temporal and spatial displacements. But current approaches to representational and cultural history often neglect to examine these technologies. James Lastra seeks to remedy this neglect. Lastra argues that we are nowhere better able to track the relations between capital, science, and cultu.
Keywords: Sound motion pictures -- History.; Sound -- Recording and reproducing -- History.; Films sonores -- Histoire.; Son -- Enregistrement et reproduction -- Histoire.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Sound motion pictures; Sound -- Recording and reproducing; Filmtechnik; Tonfilm; USA; History